POTENSI PAJAK HOTEL DI KOTA GORONTALO - Sardjono, Olivia Y. M.; Ilat, Ventje; Warongan, Jessy D. L. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
Optimization of PAD resources needs to be done to improve the ability of the region to support the implementation of regional autonomy. Hotel Tax is a tax that has the potential to develop the tourism sector in Gorontalo City. The problem in this study is that the largest source of Gorontalo city revenue from 2015-2019 still comes from the Balance Fund post which shows the level of dependency on central funds is still high. For this reason, the writer is interested in researching about the "Potential of Hotel Taxes in Gorontalo City". The purpose of this study was to determine the potential, effectiveness and potential trends of hotel tax revenues in the city of Gorontalo. This research uses a quantitative descriptive approach. The data used in this study are time series data obtained from the Gorontalo City Finance Agency and Gorontalo City Central Statistics Agency and Gorontalo Province Central Statistics Agency. Data collection method used is the documentation method with the analysis of the calculation of the potential, effectiveness and trends of hotel taxes in Gorontalo City. The type of data used are primary data and secondary data in the form of time series data from 2015-2019 (5 years). The results showed that during the period of 2015 to 2019, the target and realization of hotel tax revenues had never exceeded the potential of hotel tax revenues. There is even a difference of Rp.27,837,716,932.00 between the hotel tax revenue target set by the Gorontalo City Government and the calculation of the potential for hotel tax revenue in Gorontalo City. The effectiveness of hotel tax in Gorontalo City during the 2015-2019 period is included in the effective category. The trend equation shows that for the following years the potential for hotel tax revenues tends to increase normally. Conversely, the trend equation shows that for the following years the potential for hotel tax revenues tends to decrease in the state of the Covid-19 pandemic. Whereas if the Covid-19 vaccine was discovered in January 2021, the calculation of the estimated potential gave a sharply decreasing result in 2020 and returned to normal in 2021 until 2024.